PERAN PETUGAS GUNA MEMINIMALISIR GESEKAN ANAK BINAAN TINDAK PIDANA KRIMINAL TAWURAN ANTAR PERGURUAN SILAT PADA LPKA KLAS I BLITAR - Mukti, Muhammad Aji Trisna; Subroto, Mitro (Universitas Nusa Cendana, 2024)
Correctional Officers are coaches and mentors at the Correctional UPT. One example is the correctional officers at LPKA who have the task of developing, supervising, guiding and maintaining the security and safety of the inmates to improve and develop the students' attitudes and knowledge in a directed and regular manner to make them good and useful people so they can live in society. This research aims to explore the role of officers in efforts to minimize friction between assisted children who are involved in criminal acts, especially brawls between silat schools, at the Blitar Class I Children's Special Development Institute. Conflicts between students, especially those from silat schools, can become a serious problem threatening security and order within the LPKA environment. In carrying out this role officers use individual and group methods. Officers can apply several examples of methods, including spiritual, intellectual, and skills development methods for increased cooperation between the LPKA and the silat schools operating within it. This collaboration can help in monitoring and controlling students involved in brawls. Apart from that, providing training and coaching by officers to assist children engaged in silat schools can be a proactive step to reduce potential conflicts and friction that may still occur within due to the aftermath of the incident. Keywords: LPKA Officers; Assisted Children; Development ; Silat School